On a Long Neglected Player: The Religious Factor in Poverty Alleviation: The Example of the So-Called ‘Prosperity Gospel’ in Africa - Schliesser, Christine (Exchange, 2014)
Much of poverty alleviation theory and practice fails to sufficiently consider the following crucial factor: the religious dimension. This paper elaborates this thesis by focusing on the African context and the valuable resources African religious communities and movements can provide in the struggle against poverty. One particularly influential streak of present-time African religiousness serves as a case study: the so-called ‘Prosperity Gospel’ as part of Pentecostal Christianity. The author first argues for the continuing formative influence of religion on African conceptions of self, other, and world. Secondly, she provides a critical assessment of the impact of Pentecostalism and the ‘Prosperity Gospel’ on poverty alleviation. In comparison with secular ngos, Pentecostal churches emerge as the more effective agents of change. A third part situates the insights gained into a wider perspective, seeking ways to integrate the religious factor into a more holistic conception of and engagement against poverty
free
Keywords: African Christianity; African traditional religions; Pentecostalism; Prosperity Gospel; development; ngos; poverty alleviation